2021
DOI: 10.3389/fnut.2021.627011
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Pre-school Children and Determinant Factors of Autism: A Case-Control Study

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder triggered by several factors, including those of genetic and environmental nature. ASD can alter communication, behavior, and children's nutritional status, placing them at high risk for nutritional imbalances. Therefore, this study aims to assess preschool autistic children's nutritional status as compared to that of Typically Developing (TD) children of the same age. The study also revealed some of the ASD risk factors among the Jordanian popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
2
14
1
2
Order By: Relevance
“…Children with ASD showed a lower amount of vitamin Children with ASD in Egypt did not meet the recommendation of protein in comparison to children without ASD (Meguid et al, 2017), which is similar to the present study. In contrast, fat intake in children with ASD in Jordan was higher than children without ASD (Alkhalidy et al, 2021). Autistic children had excessive fat consumption compared to healthy children (Marí-Bauset et al, 2017), which is different from the present study.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Children with ASD showed a lower amount of vitamin Children with ASD in Egypt did not meet the recommendation of protein in comparison to children without ASD (Meguid et al, 2017), which is similar to the present study. In contrast, fat intake in children with ASD in Jordan was higher than children without ASD (Alkhalidy et al, 2021). Autistic children had excessive fat consumption compared to healthy children (Marí-Bauset et al, 2017), which is different from the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…In Spain, children with ASD also exhibited a higher intake of iron than children without ASD (Marí-Bauset et al, 2017).Previously, other studies showed that autistic children consumed lower energy and all macronutrients in comparison to children without ASD(Neumeyer et al, 2018; Liu et al, 2016). In contrast to our study, a case-control study found that carbohydrate intake among children with ASD was lower than children without ASD(Alkhalidy et al, 2021). Similar results were reported among children in Spain (Marí-Bauset et al, 2017).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The latest research by Alkhalidy et al ( 31 ) shows that autistic boys were at higher risk of inadequate vitamin K status than TD children. The proportion of boys with ASD with insufficient vitamin K intake was 86.1%, which was significantly higher than that of boys in the TD group (61.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Çocuğun mevcut durumuna ve gereksinimlerine uygun şekilde planlanmış bir eliminasyon diyeti, otizm semptomlarının ve ortaya çıkan gastrointestinal bozuklukların giderilmesini sağlayabilir. Bu nedenle ebeveynlerin veya çocuğun bakımından sorumlu olan kişilerin, beslenme tedavisinin yararları ve takibinin önemi konusunda bilinçli olmaları gerektiği bildirilmiştir [9]. OSB'li çocukların ebeveynleri ile yürütülen bir çalışmanın sonuçlarına göre, ebeveynlerin yemek zamanlarında sıklıkla zorluk yaşadıkları ve çocuklarının beslenme alışkanlıkları konusunda endişelendikleri saptanmıştır [10].…”
Section: Introductionunclassified